2002
DOI: 10.1002/jsfa.1197
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of folate losses in soybean during the preparation of tempeh and soymilk

Abstract: The changes in undeconjugated and total folate content of soybean during various stages of tempeh and soymilk preparation were studied. Total folate was extracted by the tri-enzyme technique. The ratio of total folate to undeconjugated folate was compared in all samples. Raw soybeans used for tempeh and soymilk preparation contained 4.04 and 4.50 mg total folate kg À1 respectively. Soaking and boiling soybean caused a significant loss of folate during tempeh and soymilk preparation. Leaching was identified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
(21 reference statements)
4
17
0
1
Order By: Relevance
“…During the analysis of the commercial noodles reported here, both free and total folate contents were measured, reflecting the approach used in many recent studies (Rader and others 1998, 2000; Shrestha and others 2000; DeVries and others 2001; Arcot and others 2002a, 2002b, 2002c; Johnston and others 2002a, 2002b). In summarizing the data, the proportion of free folate found was similar, and higher proportions were found in most of the dried noodles (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…During the analysis of the commercial noodles reported here, both free and total folate contents were measured, reflecting the approach used in many recent studies (Rader and others 1998, 2000; Shrestha and others 2000; DeVries and others 2001; Arcot and others 2002a, 2002b, 2002c; Johnston and others 2002a, 2002b). In summarizing the data, the proportion of free folate found was similar, and higher proportions were found in most of the dried noodles (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The loss found in egg and fish could be due to the presence of polyglutamyl tetrahydrofolate (5-methyl-THF), which is the major unstable form of folate in these foods (Konings et al, 2001). On the other hand, the major forms of folate in soybean being naturally stable (having about 50% of folate monoglutamate and 42% of 5-formyl tetrahydrofolate, as referenced by Arcot et al, 2002b), the high retention of folate in cooked soybean was expected. A loss of 25% folate in cooked soybean was found in the present study.…”
Section: Effect Of Household Cooking On Folate Retention In Various Fmentioning
confidence: 93%
“…The fermentation is caused by air-borne wild yeast extremely rich in folate, contributing to the increase (Desikachar et al 1960). Similar studies with breads and tempe have reported twofold to fourfold higher folate values due to the fermentation process (Murata et al 1970;Hawkes and Villota 1989;Arcot et al 2002). Black gram dhal, an important component of both idli and dosa batters, is a good source of folate (132 mg/100 g in the raw) (Gopalan et al 2002).…”
Section: Resultsmentioning
confidence: 81%